Prevalence of sarcopenia in geriatric hospitalized patients - Smoliner, Christine; Sieber, Cornel; Wirth, Rainer (Journal of the American Medical Directors Association, 2014)
Sarcopenia, a common syndrome in older individuals, is characterized by a progressive loss of muscle mass and muscle strength. Although data exist on the prevalence of sarcopenia in community-dwelling older individuals and nursing home residents, there has been no systematic research in hospitalized older patients according to newly developed criteria.Cross-sectional study design.Acute geriatric ward of a general hospital.Geriatric inpatients.Hand grip strength was measured with the Jamar dynamometer, skeletal muscle index was calculated from raw data obtained from the bioelectrical impedance analysis, and physical function was assessed with the Short Physical Performance Battery. Sarcopenia was defined according to the criteria of the European Working Group on Sarcopenia in Older People (EWGSOP).This study involved 198 patients from a geriatric acute ward. Mean age was 82.8 ± 5.9 years and 70.2% (n = 139) of the study participants were women. Thirteen patients (6.6%) were defined as sarcopenic and 37 (18.7%) were defined as severely sarcopenic. In a group comparison, patients with sarcopenia had a poorer nutritional status. In a binary logistic regression analysis, only body mass index was associated with sarcopenia, whereas gender, age, length of stay, cognitive function, and self-care capacity were not.The prevalence of sarcopenia in geriatric hospitalized patients is high and does not differ from those of other older individuals. Nutritional status is associated with sarcopenia. The predictive value of sarcopenia regarding outcome for older individuals still requires evaluation.
EVALuna2:10508